HUKUM DAN KEKERASAN DI SEKOLAH: OPTIMALISASI PERAN KONSELOR SEKOLAH - Nurochim, Nurochim; Ngaisah, Siti (SASI, 2020)
Violence in the school environment is still a problem that requires multi-sectoral solutions. The school is an organization as a place to gather for a long time. Interactions in schools are multistrata interactions such as differences in the social backgrounds of students, teachers, and education personnel. The method used in this article is literature review. The results of the study in this study are school counselors have an important role in developing social attitudes of school residents with programmatic counseling activities. The counseling program is implemented to provide rights and obligations for school residents. By having a social attitude, conflicts between school members can be prevented. Counseling activities are organized as preventive and curative activities from violence in schools.